AKTIVITAS EKSTRAK DAN FRAKSI DAUN PIDADA MERAH (SONNERATIA CASEOLARIS L.) SEBAGAI ANTIOKSIDAN - Herwinda Suprianto; Muhamad Amir M (PROSIDING SEMINAR KIMIA, 2013)
A research has been conducted with a title .The activity of extract and fractions of Sonneratia leaf (Sonneratia caseolaris L.) as an antioxidant. This research aims to know the activity of extract and fractions of Sonneratia leaves as an antioxidant against the free radical DPPH. The Sonneratia leaves powder was extracted using maceration tool with methanol solvent. The methanolic extract fractioned with n-hexane, ethyl acetate, and n-butanol solvents. Testing of antioxidant activity is performed with the DPPH method (1,1-Diphenyl-2-Picrylhydrazyl) by spectrophotometry. Absorbance measurement was conducted with spectrophotometry at the wave length 516 nm. Data was analyzed with linear regression to obtain values of IC50. The result of research showed that the extract and fractions of Sonneratia leaves have activity as an antioxidant with the IC50 value of methanolic extract was 21,62 ppm, n-hexane fraction was 82,36 ppm, ethyl acetate fraction was 13,41 ppm, and n-butanol fraction was 13,04 ppm. The test samples which provide the best antioxidant activity is the fraction of n-butanol.